Development and validation of an online calculator to predict early recurrence and long‐term survival in patients with distal cholangiocarcinoma after pancreaticoduodenectomy. (5th November 2021) - Xu, Shuai; Zhang, Xiu‐Ping; Zhao, Guo‐Dong; Zhao, Zhi‐Ming; Gao, Yuan‐Xing; Hu, Ming‐Gen; Tan, Xiang‐Long; Liu, Rong
Abstract: Background: Distal cholangiocarcinoma (DCC) is a malignancy associated with a short survival time. In this study, we aimed to create an online nomogram calculator to predict early recurrence and long‐term survival in patients with DCC after pancreaticoduodenectomy. Methods: A total of 486 patients with DCC were included. An online nomogram calculator was developed and validated in training, internal validation and external validation cohorts, respectively. Results: Of the 486 patients who met the inclusion criteria, we allocated 240, 120, and 126 patients to the training, internal validation, and external validation cohorts, respectively. Multivariable analysis showed that preoperative CA19‐9, maximum tumor diameter, perineural invasion, and tumor differentiation were significant risk factors for early recurrence in patients with DCC. Incorporating these four factors, the nomogram achieved good AUC values of 0.788, 0.771, and 0.723 for predicting early recurrence in the training, internal validation, and external validation cohorts, respectively. Notably, this nomogram also had good power to predict overall survival. The discrimination ability of the nomogram was evaluated by dividing the predicted probabilities of early recurrence and survival into two risk groups in the training cohort (low risk ≤ 132; high risk > 132; P < .001). Time‐dependent ROC and decision curve analysis further revealed that the nomogram provided higher diagnostic capacity and superior net benefit compared to other staging systems. Conclusion: This study developed and validated a web‐based nomogram calculator that was capable of predicting early recurrence and long‐term prognosis in patients with DCC after pancreaticoduodenectomy with high degrees of stability and accuracy.